2013
DOI: 10.3109/0886022x.2013.846831
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of surfactant protein A and D expression decrement and their localizations in human prostate adenocarcinomas

Abstract: The development of prostate cancer may be related to decreased level of surfactant protein A and D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(33 reference statements)
2
8
0
1
Order By: Relevance
“…This fact has already been described for other tissue and results from intensive post-translational processing of the surfactant proteins [ 20 , 21 ]. As the presence of surfactant proteins within human and murine prostate has qualitatively already been described by others the corresponding results of this study are not entirely novel [ 22 24 ]. As the intensity of the protein bands obtained in the Western blot experiments does not stoichiometric correlate with the protein concentration only subjective quantification would be possible.…”
Section: Discussionsupporting
confidence: 81%
“…This fact has already been described for other tissue and results from intensive post-translational processing of the surfactant proteins [ 20 , 21 ]. As the presence of surfactant proteins within human and murine prostate has qualitatively already been described by others the corresponding results of this study are not entirely novel [ 22 24 ]. As the intensity of the protein bands obtained in the Western blot experiments does not stoichiometric correlate with the protein concentration only subjective quantification would be possible.…”
Section: Discussionsupporting
confidence: 81%
“…Lysate proteins (30 μg) were separated on 15% SDS-PAGE polyacrylamide gel and electrophoretically transferred onto PVDF membranes (Pall Corporation, NY, USA). The blot was probed with primary antibodies raised against human SP-D [a gift from Uffe Holmskov, (13)], Phosphorylated-p53 (Ser 15) (Cell Signaling Technology), pAKT (PathScan® Multiplex Western Cocktail I), pan Akt (ABclonal), phospho-Bad-S155 (ABclonal), Bcl-2 associated death promoter (Bad) (Apoptosis I sampler Kit), Bcl-2-associated X protein (Bax) (Apoptosis I sampler Kit), B-cell lymphoma 2 (Bcl2) (Apoptosis I sampler Kit) or caspase 7 (Cell Signaling Technology), followed by HRP-conjugated secondary antibodies. All western blot images were acquired by Syngene (Chem Genius) and quantified by Syngene Gene Tools.…”
Section: Methodsmentioning
confidence: 99%
“…Elevated levels of SP-D at inflamed sites in the prostate manifested protection against bacterial infection (11, 12). Kankavi et al (13) observed differential expression of SP-D in glandular structures of inflamed malignant and non-malignant human prostate tissues. There was a significant correlation between decreased levels of SP-D and increased Gleason score, a grading system based on the histologic pattern of arrangement of carcinoma cells, and tumor volume.…”
Section: Introductionmentioning
confidence: 99%
“…A monoclonal SP-D antibody showed the band at 43 kDa in sperm. The same group then followed with an in depth study to determine how surfactant proteins are altered in prostate adenocarcinomas (Kankavi et al, 2014). Protein expressions were tested by IHC and Western blots.…”
Section: Review Of the Localization And Known Functions Of Extra-pmentioning
confidence: 99%